Aplikasi E-Commerce Berbasis Web Untuk Umkm Kerajinan Tangan Di Cikarang - Ergi Hermawan (Prosiding Sains dan Teknologi, 2022)
The background of this research is the lack of promotional media for a product in Cikarang. Therefore, more and more means of marketing goods are starting to use the E-Commerce system as an online sales medium. In the process of building an ECommerce website, it uses a life cycle development technique or can be called a waterfall. The goal to be achieved from the development of this E-Commerce system is to make it easier for buyers to make transactions wherever buyers are without having to come to the store. Keywords: E-Commerce; Laravel; Web-based application; Online store